Relationship between clinical severity and hours of nursing care in an emergency room - Simone Silva Sabino; Laura Menezes Silveira; Angelita Maria Stabile (Universidade Federal do Ceará, 2020)
Objective: to evaluate the relationship between the clinical severity of the patients and the hours of care of nursing professionals in an emergency room. Methods: correlational study, which used the Nursing Activities Score and Acute Physiology and Chronic Health Evaluation I instruments. Results: we included 338 patients. The highest averages were identified in the group related to deaths, with (22.0%) for Acute Physiology and Chronic Health Evaluation II and (56.8%) for Nursing Activities Score, (p=0.000). We obtained a moderate relationship between these scores. Moreover, the two instruments used proved to be capable of predicting deaths. Conclusion: evaluations of the worsening of patients and the demand for care can contribute to the adequacy of the number of personnel, the reduction of the length of stay in the emergency rooms and the high-quality care planning.